Wasilah and Tawhid in QS. Al Maidah [5]:35: Study the Book of Mafahim Yajibu an Tusahhah - Muhammad Rifqi Zainul Alam; Ulfah Rahmawati (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This article analyzes the meaning of wasilah and tauhid in QS al-Māidah [5]:35 according to the interpretation of Sayyid Muhammad Alawi al-Maliki in the book Mafahim Yajibu an Tusahhah. The focus of the study is on understanding tawassul as a means of drawing closer to Allah without contradicting the principle of tauhid. This study uses a qualitative method with a literature review approach. The book Mafahim Yajibu an Tusahhah is used as the main source, while classical interpretations and contemporary academic literature are used for analysis. The results of the study show that, according to Sayyid Muhammad Alawi, tawassul through the prophets, righteous people, and good deeds is not a form of shirk, but a practice that is in line with tawhid. This view emerged as a response to groups that reject tawassul on the grounds of bid'ah and shirk. Thus, this study demonstrates the relevance of tawassul in enriching contemporary thematic tafsir studies while strengthening the discourse of religious moderation among Muslims. It is hoped that the results of this research can contribute to the development of thematic interpretation studies, especially in strengthening moderate understanding of the practice of tawassul in the contemporary Islamic context.